Usability of social media platform for business development / Harry Ray Usah - Usah, Harry Ray (Perpustakaan Tun Abdul Razak, Universiti Teknologi MARA Sarawak, 2022)
In this article analysis and task that were given we are trying to find out and figure out the the relations of business records management and and social media as both of the topic are being gather which it’s were focuses on the result of making this decision, by that in business development and social media it were being used widely in this modern day as technology were having an transformation from day to another day. Business records management one of the title or activity that are very important to implied in business daily practices which every records that are going to be stored and kept need to have a proper records style which this may lead to the good business record management activities beside, social media will become one of the medium that are going to be used as the promoting tools for business development and in the same time it might cut the cost rather than using traditional promotion method. Based on the article that are chosen which has been given the title as (Usability of Social media for business development), where this topic need us to be more creative and more innovative in promoting business development and identified the usability of Social Media for business development in this modern days. Usability of social media and business development were being gathered as this will be ensured to produced one compacts result in the way to make use or fully utilized the technology that are available too.